Multilateral agreement contract optimization of renewable energy power grid-connecting under uncertain supply and market demand - Lingcheng, Kong; Zhenning, Zhu; Jiaping, Xie; Jing, Li; Yuping, Chen (Computers & industrial engineering, 2019)
•Renewable energy power pricing under uncertain supply and demand.•Renewable energy electricity supply chain collaboration.•Introducing government subsidies as a decision variable into the collaboration model.•Impact of demand price elasticity on supply chain collaboration. Renewable energy electricity is being developed and utilized on a large scale in many countries because of the fossil fuel pollution and the energy shortage. But the uncertainty of renewable energy output caused by intermittency, as well as the uncertainty of consumers’ electricity demand both bring difficulty to the grid-connection even with government support. There are interest conflicts between the power producer and grid company under the government’s fixed-pricing mechanism in renewable energy market. Therefore, this paper takes uncertainties of output and demand as well as the government subsidy into consideration, and then solves the problems of power grid-connection by designing a revenue-sharing contract between upstream and downstream enterprises. In this supply chain model which consists of one type of upstream firms, power generators, and a single dominant downstream grid company, the government plays a third-party role and subsidizes all the firms based on the grid-connected quantity. Consequently, the theoretical research and numerical simulation show that the revenue-sharing contract can realize the collaboration of renewable energy supply chain effectively with different market demand price elasticity. The profits of all supply chain members and the sales price both decrease with the growth of price elasticity in a lower range. Meanwhile, renewable energy power investment is hindered dramatically by a higher price elasticity. The results figure that the revenue-sharing contract is mainly influenced by the grid-connected wholesale price, the output intensity of renewable energy and the government subsidy. Specially, the revenue-sharing ratio of grid will exceed 80% when the renewable power generators receives all the government subsidies. This study provides an alternative approach for the renewable energy grid-connection and the power supply chain collaboration.